2018
DOI: 10.1177/1477370818819216
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in political aggression: The role of social integration, perceived grievances and low self-control

Abstract: Several models have been suggested for studying (self-reported) aggression. Less frequently, these theories are empirically applied to explain individual differences in political aggression. The present study examines the role of distal, intermediate and proximate mechanisms in a net-sample of 6020 young adults. Using log-linear structural equation modelling, the independent effects of cumulative social integration, perceived personal and group injustices and low self-control are assessed. It is assumed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 86 publications
0
15
0
Order By: Relevance
“…Seven studies that were reviewed identified significant associations between radicalisation and terrorist behaviour and sensation, risk, and thrill-seeking traits (De Waele & Paulwels, 2016;Egan, et al, 2016;Nussio, 2017;Pauwels & Hardyns, 2018;Paulwels & Heylen, 2014;. Relatedly, six studies also identified impulsivity and poor self-control as a common trait across adolescents, young adults, and extremists Pauwels & De Waele, 2014;Pauwels, et al, 2020;Pauwels & Svensson, 2017;Perry, et al, 2018;. 22 Another trait that is strongly associated with psychopathy is low empathy.…”
Section: Personality Traits 20mentioning
confidence: 99%
“…Seven studies that were reviewed identified significant associations between radicalisation and terrorist behaviour and sensation, risk, and thrill-seeking traits (De Waele & Paulwels, 2016;Egan, et al, 2016;Nussio, 2017;Pauwels & Hardyns, 2018;Paulwels & Heylen, 2014;. Relatedly, six studies also identified impulsivity and poor self-control as a common trait across adolescents, young adults, and extremists Pauwels & De Waele, 2014;Pauwels, et al, 2020;Pauwels & Svensson, 2017;Perry, et al, 2018;. 22 Another trait that is strongly associated with psychopathy is low empathy.…”
Section: Personality Traits 20mentioning
confidence: 99%
“…This might explain why so many extremist groups hold conspiracy beliefs. Conspiracy theories may fulfil basic needs which many extremists have been shown to strive for, such as the ability to provide certainty and cognitive closure Webster & Kruglanski, 1994) and overcome issues related to perceived powerlessness and feelings of anomia (Boehnke, Hagan, & Merkens, 1998;Pauwels, Ljujic, De Buck, 2018).…”
Section: Existential and Epistemic Needsmentioning
confidence: 99%
“…Low self-control has proven to be a relatively robust risk factor for criminal and violent behaviors (Pratt and Cullen 2000;Vazsonyi et al 2017). While Hirschi and Gottfredson (2001) initially theorized that self-control is not relevant for understanding ideologically-motivated offenders because committing terrorist attacks requires long-term planning and foresight, studies have shown that low self-control is a relatively robust risk factor for violent extremist outcomes (Pauwels and De Waele 2014;Pauwels and Svensson 2017;Pauwels et al 2018;Rottweiler et al 2021;Wolfowicz et al 2019). Although conceived as a time-stable trait that accounts for between-individual differences in criminal behavior, there is growing evidence that low self-control is malleable over the life course, and that within-individual changes in low self-control can explain changes in criminal behavior (Burt et al 2014;Hay et al 2010;Huijsmans et al 2019).…”
Section: Radicalization and Individual Characteristicsmentioning
confidence: 99%